Squint - Mohd Isa, Muhammad; Talib, Norlaila; Othman, Othmaliza; Chu, Kieu Ching (Universiti Putra Malaysia Press, 2017)
Sight is a precious gift, which at times we take for granted. The eyes are our windows to the wonders of the world. The reflected light of an object we are looking at, enters the eye through the crystal clear cornea. The light then passes through the aqueous humour.